Gen Zers' intention to purchase products with sustainable packaging: an alternative perspective to the attitude-behaviour gap. Issue 9 (13th June 2022) - Lisboa, Ana; Vitorino, Liliana; Antunes, Raquel
ABSTRACT: Environmentally aware consumers are a reality. Young consumers, specifically Gen Zers, are key given their role in sustainable behaviour and in influencing their peers and other generations. In purchases of everyday products, consumers may rely on immediate cues to facilitate their decisions. Additionally, they may face trade-offs between eco-friendliness and the product's perceived convenience and usability. The study investigates the influence of Gen Zers' perceptions of packaging sustainability and ergonomics in their environmental attitude and intention to purchase products. It provides an alternative perspective to the attitude-behaviour gap and managerial insights regarding packaging as an information cue to everyday products.